2012
DOI: 10.5114/kitp.2012.32694
|View full text |Cite
|
Sign up to set email alerts
|

JAKOŚĆ W MEDYCYNIE Depression in chronic heart failure

Abstract: Chronic heart failure (HF) is one of the most challenging problems in cardiology. Depression often coexists with HF. It can develop at any stage of heart disease: as a response to the diagnosis, disease exacerbation or poor prognosis. There is evidence of common pathophysiological pathways in the two diseases: neurohormonal stimulation, arrhythmias, inflammation and blood hypercoagulability. Although the correlation between depression and poor HF prognosis is well recognised, it is still uncertain whether depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(40 reference statements)
1
3
0
Order By: Relevance
“…Illness acceptance is a prerequisite for effective coping with the consequences of disease, and is a determinant of HRQOL. 11,35 In the present study, comparative analysis of HRQOL based on AIS scores showed that patients with high acceptance of illness also have higher HRQOL scores in the WHOQOL-BREF (physical, social and environmental domains) and ASTA HRQOL scale, and a lower intensity of symptoms as measured by the ASTA symptom scale. A positive impact of acceptance of illness on HRQOL has also been shown in single-factor analysis, improving scores in all WHOQOL-BREF domains except psychological and in the ASTA HRQOL scale.…”
Section: Factor (Variable)supporting
confidence: 50%
See 1 more Smart Citation
“…Illness acceptance is a prerequisite for effective coping with the consequences of disease, and is a determinant of HRQOL. 11,35 In the present study, comparative analysis of HRQOL based on AIS scores showed that patients with high acceptance of illness also have higher HRQOL scores in the WHOQOL-BREF (physical, social and environmental domains) and ASTA HRQOL scale, and a lower intensity of symptoms as measured by the ASTA symptom scale. A positive impact of acceptance of illness on HRQOL has also been shown in single-factor analysis, improving scores in all WHOQOL-BREF domains except psychological and in the ASTA HRQOL scale.…”
Section: Factor (Variable)supporting
confidence: 50%
“…Illness acceptance is a prerequisite for effective coping with the consequences of disease, and is a determinant of HRQOL. 11,35…”
Section: Discussionmentioning
confidence: 99%
“…Acceptance of illness represents a compromise between one's vulnerability and resistance to a disease, thus being a prerequisite of efficient coping with consequences of the latter and an important determinant of QoL. 8,9 Evaluation of QoL perceived by HF patients enables one to detect specific problems inherent to this condition, and to implement appropriate, individualized intervention. Self-acceptance of health status modulates either one's level of activity or his/her QoL.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the considerable advances in pharmacological and interventional treatment, chronic heart failure (CHF) still remains a significant clinical problem associated with high mortality and frequent hospitalization. Depression is a serious and modifiable concomitant of CHF and it is one of the main causes of cognitive dysfunctions and patient noncompliance [ 1 3 ]. It can occur at any stage of CHF, as a reaction to: diagnosis, imposed change of lifestyle, sudden exacerbation of symptoms or poor prognosis.…”
Section: Introductionmentioning
confidence: 99%